What Drives Bank-Intermediated Trade Finance? Evidence from Cross-Country Analysis - Jose Maria Serena Garralda; Garima Vasishtha (Bank of Canada, 2015)
Empirical work on the underlying causes of the recent dislocations in bank-intermediated trade finance has been limited by the poor availability of hard data. This paper analyzes the key determinants of bank-intermediated trade finance using a novel data set covering ten banking jurisdictions. It focuses on the role of global factors as well as country-specific characteristics in driving trade finance. The results indicate that country-specific variables, such as growth in trade flows and the funding availability for domestic banks, as well as global financial conditions and global imports growth, are important determinants of trade finance. These results are robust to different model specifications. Further, we do not find that trade finance is more sensitive to global financial conditions than other loans to non-bank entities.
Keywords: F14; F19; 330; International topics; International financial markets; Econometric and statistical methods